Protect and defend : a thriller - Flynn, Vince (New York : Atria Books, 2007)
In the aftermath of an Israeli attack on Iranian nuclear facilities, CIA director Irene Kennedy and operative Mitch Kelly are dispatched to the Middle East to diffuse Iran's sworn retaliation against the United States.
Keywords: Rapp, Mitch (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Terrorism -- Fiction; Iran -- Fiction; Political fiction; Suspense fiction